Putative Criteria for Predicting Spontaneous Regression of Prenatally Diagnosed Thoracoabdominal Cystic Lesions - Lecompte, Jean-Francois; Hery, Geraldine; Potier, Alain; Gorincour, Guillaume; Giudicelli, Béatrice; Philip, Nicole; Guys, Jean-Michel; de Lagausie, Pascal (European Journal of Pediatric Surgery, 2014)
Purpose Cystic lesions are common findings during prenatal ultrasonography but their prenatal and postnatal prognosis is difficult to establish because of some regress spontaneously. The purpose of this study was to identify putative criteria to predict regression of partially or completely cystic lesions detected by prenatal ultrasound.Methods Prenatal ultrasound features of thoracic or abdominal cystic lesions were retrospectively analyzed. Ovarian and urological lesions were not included in this study.Results A total of 57 cystic lesions were studied. Of the 57 lesion, 36 lesions including 10 abdominal (43.5%) and 26 thoracic (76.5%) lesions required surgical resection. Of the 57 lesions, 10 persistent lesions after birth were only monitored. Eleven lesions including eight abdominal (34.7%) and three thoracic (8.8%) lesions regressed prenatally (p = 0.02). Regressing abdominal lesions consistently presented as solitary lesions with a homogenous aspect. Only one abdominal lesion showed a multilobulated aspect. Two regressing thoracic lesions were purely cystic and one lesion presented a heterogeneous aspect.Conclusion Regression of cystic lesions detected by prenatal ultrasound scan was more likely for lesions in abdominal (mainly adrenal or splenic lesions) than thoracic locations. The likelihood of regression was highest for purely cystic abdominal lesions.
Keywords: cystic lesions; regression; prenatal; ultrasonography